Ontogenetic criteria to distinguish vertebral types on the debated xenarthran synsacrum - Galliari, Fernando Carlos (2014)
The presence of a synsacrum formed by the fusion of vertebrae that come into closed contact with the ilium and ischium is a feature that characterizes the clade Xenarthra. Nevertheless, the proper identity of each vertebral element that forms it is a matter of discussion. In this article, we provide ontogenetic information about skeletal ossification of the xenarthran synsacrum and define the position of the sacrocaudal limit within it. We analyzed the synsacrum of 25 specimens of nonadult and 101 adult armadillos and anteaters: Dasypus hybridus, D. novemcinctus, Chaetophractus vellerosus, C. villosus, Tamandua tetradactyla, and Myrmecophaga tridactyla. Two sets of vertebrae were identified: an anterior set, often attached to the iliac bones, in which transverse processes are originated mainly from an expansion of the base of the neural arches, and secondarily from a lateroventral ossification center. A posterior set is characterized by a series of vertebrae along which extra lateral ossifications (described here for the first time) are developed and form exclusively the transverse processes. Among armadillos, the sacrocaudal limit is set between the last vertebrae attached to the iliac bones and the first vertebrae that form the dorsal border of the sacroischial fenestra. In addition, anterior free caudals also showed extra lateral ossifications forming exclusively the transverse processes, supporting the notion that more posterior synsacrals are in fact caudal vertebrae that were incorporated to the synsacrum. In pilosans, the sacrocaudal limit is set between the first vertebrae that come into contact with the ischial bones and the immediately anterior one. However, the pattern of homologies is obscured by the low resolution in the ontogenetic sequence when compared to that of armadillos.